(untitled) - Uys, Pieter Hendrik Schalk

The effect of feed processing and nutrient density level on the growth rate, feed conversion, rumen fermentation parameters and economy of finishing lambs (Stellenbosch : Stellenbosch University, 2022)
Thesis (MScAgric)--Stellenbosch University, 2022.